The different predictive value of mean platelet volume-to-lymphocyte ratio for postoperative recurrence between non-muscular invasive bladder cancer patients treated with intravesical chemotherapy and intravesical chemohyperthermia - Wang, Chengbo; Jin, Wenjun; Ma, Xiaodong; Dong, Zhilong (Frontiers in Oncology, 2023)
Introduction. The inflammatory response plays a potential role for postoperative recurrence in patients with non-muscular invasive bladder cancer (NMIBC). We aimed to investigate whether PLR, MPVLR, and SII have prognostic value in NMIBC treated with conventional intravesical chemotherapy or intravesical CHT and the difference between them. Materials and Methods. A retrospective cohort study was conducted in 222 patients with NMIBC treated with Intravesical Chemotherapy or Intravesical CHT between January 2016 and December 2020. PLR, MPVLR and SII were obtained based on routine blood settlement within a week before surgery. The receiver operating characteristic curve was used to determine the optimal cutoff value of each index and different groups were grouped accordingly. Kaplan- Meier survival curve and Cox regression model were used to study the factors affecting the prognosis of NMIBC patients in different treatments. Results. 69 cases (46.3%) in GEM group had tumor recurrence and 19 (12.8%) of them progressed to MIBC or got metastasis, while 19 cases (26.0%) in CHT group recurred and 2 (2.7%) progressed. Elevated PLR, MPVLR and SII were associated with higher recurrence rate in the GEM group and PLR and MPVLR were the independent risk factors. While in the CHT group, high PLR and SII were related to postoperative recurrence and none of them were independent risk factors. Conclusion. The preoperative clinical inflammatory indexes PLR, SII, and MPVLR have certain predictive value for postoperative RFS in NMIBC patients treated with intravesical chemotherapy while PLR and SII can predict the prognosis of NMIBC patients treated with intravesical CHT, which indicates that intravesical CHT may stop tumor recurrence by influencing the effect of mean platelet volume on tumor growth through some unknown mechanisms.